Impulsive generation of 100 dislocation loops in BCC iron - Bertoni, Andrés Ignacio (2020)
The conditions for the formation of 100 dislocation loops in body-centered cubic (BCC) iron were investigated via molecular dynamics simulations using a simplified model intended to mimic conditions in high energy collision cascades, focusing on the possible coherent displacement of atoms at the boundary of a subcascade. We report on the formation of 100 dislocation loops due to the fast displacement of a few hundred atoms with a coherent acceleration, in agreement with previous results for much larger cascade simulations. We analyze in detail the resulting atomic velocities and pressures, and find that they cannot be described within the usual formalism for a shock regime, since the pressure pulse only lasts less than 1 ps and does not match expected values from a Hugoniot shock. Our simulations include two interatomic potentials: Mendelev, which is extensively used for radiation damage simulations, and Ackland, which has been used for shock simulations because it can reproduce the experimentally observed transition from BCC to hexagonal close-packed structure at around 25 GPa, at high deformation rates. They both show similar evolution of defects, also indicating departure from a shock regime which is extremely different for these potentials.